Current Trends in Facial Rejuvenation: An Assessment of ASPS Members' Use of Fat Grafting during Face Lifting. Issue 1 (July 2015) - Sinno, Sammy; Mehta, Karan; Reavey, Patrick L.; Simmons, Christopher; Stuzin, James M.
Abstract : Background: Fat grafting can be used to improve the results of face lifting. The extent to which plastic surgeons use fat grafting in their face-lift practices is unknown. The goals of this study were to understand the current use of fat grafting during facial rejuvenation surgery and identify the most common techniques used. Methods: A 28-item questionnaire was formulated for distribution to a randomized cohort of American Society of Plastic Surgeons members. Data were collected and statistically analyzed using Pearson chi-square and Fisher's exact tests. Results: A total of 309 questionnaires were collected. The questionnaire revealed that 85.2 percent of respondents use fat grafting during face lifts. Currently, the most common techniques used include abdominal harvest, centrifuge processing, blunt cannula injection without pretunneling, and placing less than 0.1 cc per pass. The deep central malar, lower lid cheek junction, and nasolabial folds are the most commonly injected areas. Conclusions: Combining surgical repositioning of fat with fat grafting offers surgeons a greater degree of aesthetic control for correcting contour in the aging face. Although there is controversy regarding the best method to surgically reposition fat, there is a growing consensus that volume augmentation is preferred by most face-lift surgeons. Abstract : Video Discussion by David A. Hidalgo, M.D., is available online for this article.